Taxonomical Properties of Three Verbascum L. Species and Their Antioxidant Activities - Alan, S.; Saltan, F.Z.; Gokturk, R.S.; Sokmen, M. (Asian Journal of Chemistry, 2010)
The purpose of this investigation was to determine and characterize the antioxidant activity of the 12 extracts of the aerial parts from three Verbascum L. species, of which two are endemic to Turkish Flora, utilizing the DPPH free radical-scavenging and β-carotene/linoleic acid assays. The methanol and water extracts of three Verbascum species exerted greater antioxidant activity than those of other plant extracts with an IC value of 130.8 ± 0.5, 309.3 ± 0.5, 65.4 ± 0.5, 235.6 ± 0.5, 123.8 ± 0.5 and 132.8 ± 0.5 μg/mL for V. leptocladum, V. mucronatum and V. davisianum, respectively. Furthermore, the morphological and anatomical characters of these Verbascum species were described comparatively. In two different test system, the most active plant was V. mucronatum with 65.4 ± 0.5 μg/mL and 70.4 (%) inhibition rate. Antioxidant activities of BHT were also used for positive controls. In addition, anatomical structures of root, stem and leaves of three Verbascum species are given in this study for the first time. According to results, in terms of root, stem and leaf anatomical structures of each Verbascum species, V. leptocladum differs morphologically and anatomically from the others. These differences can be summerized as follows; in stem narrower sclerenchymatic cells and phloem than those in V. leptocladum; in leaf of V. leptocladum; having a protrusion below, continuous vascular bundles, less parenchymatic cells in outer and iner epidermis, stellate type hairs and differences in the number of cells in secretion hairs.